THE ETHICS OF AL-GHAZALI'S PERSPECTIVE IN KIMIYAUS SA'ADAH AND ITS RELEVANCE TO CONTEMPORARY MORAL CHALLENGES - Irfani, Muhammad Aska; Iqbal, Imam; Nugraha, Dendi (Universitas Islam Madura, 2025)
The moral crisis characterized by value relativism and secularism demands the contribution of religious ethics that is transcendental and adaptive. This study aims to explore the ethical structure of Al-Ghazali in Kimiyaus Sa'adah and assess its relevance in responding to contemporary ethical challenges. This study uses a qualitative approach based on literature studies, with textual and hermeneutical analysis of Al-Ghazali's primary works and relevant secondary literature. The results of the study show that Al-Ghazali's ethics are based on revelation as the main source of morality, but still provide space for rationality within the framework of tafakkur and moral introspection. There is a harmonious integration between tazkiyah al-nafs, morality, and love for God, which is directed at ukhrawi happiness. This ethical system emphasizes not only formal obedience to divine law, but also inner transfiguration through the control of the passions and the actualization of the angelic nature in man. In conclusion, Al-Ghazali's ethics offers a theocentric, spiritual, and rational model of Islamic ethics, which remains relevant to be applied contextually in pluralistic and secular societies. This study opens up opportunities for the development of Islamic public ethics based on revelation that is dialogical and inclusive, as well as encouraging further research in the realms of bioethics, social justice, and ecotheology.